Effect of Integrated Nutrient Management on Seed Production of Olitorius Jute Raised from Top Cutting Method - Mandal, Probodh; Mondal, S. S.; Patra, B. C. (International Journal of Bio-resource and Stress Management, 2023)
A field experiment was conducted for two years during August-December of 2006 and 2007 to evaluate the effect of integrated nutrient management on seed production of olitorius jute (cv JRO-524) raised from top cutting with the application of N:P2O5:K2O @ 15:10:10 kg ha-1 (RD) through inorganic sources and 75% recommended dose (RD) of N, P2O5 & K2O through inorganic fertilizer along with 25%N through different sources of organic matter. The experiment was laid out in a Randomized Block Design with 9 treatment combinations replicated thrice. The treatments were 100% RDF, 75% RDF+25% N-Karanja cake, 75% RDF+25% N-Neem seed powder, 75% RDF+25% N-OM rich with humas, 75% RDF+25% N-Pelleted form of organic manure, 75% RDF+25% N-vermicompost, 75% RDF+25% N-Jatropha cake, 75% RDF+25% N-FYM and 75% RDF+Azospirillum. Among the integrated management treatments, 75% RDF+25% N-FYM proved best not only in influencing highest growth and yield but also in balancing soil nutrients.